Effect of Kind and Dosage of Enrichment Materials on the Nutritional Quality of Rotifers Especially n3-HUFA - Muhammad Agus Suprayudi (Jurnal Akuakultur Indonesia)
This experiment was conducted to evaluate the quality of rotifer enriched with four  kinds of enrichement materials from the stand point of essensial fatty acids. Rotifer was enriched at 24 - 25oC for 18 hours at a density of 1000 ind/ml.  Rotifers were treated by four kinds of enrichment materials such as oleic acid (R-OA), two different density of Nannochloropsis oculata, (4x107 and 16x107 cell/ml; R-N18 and R-N42) two different levels of eicosapentaenoic acids (EPA) triglyceride type (EPA-TAG) (20 and 40 ml/ml; R-E20, R-E40) and two different level of EPA ethyl ester (EPA-EE) (R-EE25 and R-EE50%) respectively. Rotifers enriched with Nannochloropsis oculata and EPA-EE type have a similar profile of essensial fatty acid especially on n3-HUFA that dominated by EPA, while DHA was in a trace amount or not detected.  In addition Nannochloropsis oculata as an enrichment material showed the highest population density of rotifers during enrichment periods.  Rotifer enriched with EPA-TAG has a more complete of essential fatty acid profile compared to other enrichment materials due to their contained both of EPA and DHA. We conclude that rotifer enriched with EPA-TAG as enrichment material showed the best nutritional quality of rotifers from the stand point of essential fatty acid.